Challenges facing clinical nurse educators and nursing students in Egyptian and Saudi clinical learning environment: A comparative study - Amal Ahmed Elbilgahy; Fatma Abdou Eltaib; Josephin A. Lawend (Elsevier, 2020)
Background: Clinical learning environment (CLE) was considered as an important aspect of the nursing education; but still appears that there are some problems hindering students in learning and performing effectively in the hospital. Therefore, this study aimed to discover the challenges facing clinical nurse educators and nursing students in Egyptian and Saudi clinical environment as a comparative study. Methods: A cross-sectional descriptive comparative research design was conducted for this study on a convenience sample of 285 nursing students and 45 clinical nurse educators from college of nursing, Northern Borden University, Saudi Arabia and college of nursing, Mansoura University, Egypt. Results: The results of the study showed that, the mean score for Saudi students in relation to personalization was19.20 ± 3.27 compared to 21.26 ± 5.02 for Egyptian students with highly statistically significant difference. In addition, there is no significant difference between clinical nurse educators in Saudi Arabia and Egypt with mean scores (26.95 ± 4.49 and 25.17 ± 4.24) respectively in relation to challenges related to nursing students that facing clinical nurse educators in the hospital. Conclusion: The study concluded that, there was statistical significant difference in the domains of personalization in 3rd year nursing students with higher mean score among Egyptian nursing students compared to Saudi one. Near equal mean score were observed between Egyptian and Saudi clinical nurse educators regarding challenges facing in the hospital related to students. Therefore, the researchers recommended increasing the clinical contact hours in all nursing curriculum to allow the students to be involved clinical work and participate actively.